2016
DOI: 10.1007/s10339-016-0756-7
|View full text |Cite
|
Sign up to set email alerts
|

Does finger sense predict addition performance?

Abstract: The impact of fingers on numerical and mathematical cognition has received a great deal of attention recently. However, the precise role that fingers play in numerical cognition is unknown. The current study explores the relationship between finger sense, arithmetic and general cognitive ability. Seventy-six children between the ages of 5 and 12 participated in the study. The results of stepwise multiple regression analyses demonstrated that while general cognitive ability including language processing was a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 55 publications
3
21
1
2
Order By: Relevance
“…There are conflicting findings on the relation between finger gnosis and arithmetic skills in 5 to 8 year old children, some reporting strong associations (Fayol et al, 1998;Noël, 2005), while others showing no behavioral associations (Long et al, 2016;Newman, 2016) for roughly the same age groups. Newman (2016) reported that children 5-8 failed to show a relationship between addition performance and finger gnosis, while children 9-12 did show such a relationship; finger gnosis better predicted performance in older children than younger children. The explanation provided for the discrepancy, between the two age groups on how finger gnosis relates to addition performance, was that both addition and finger sense skills are still developing in the younger group.…”
Section: Discussionmentioning
confidence: 99%
“…There are conflicting findings on the relation between finger gnosis and arithmetic skills in 5 to 8 year old children, some reporting strong associations (Fayol et al, 1998;Noël, 2005), while others showing no behavioral associations (Long et al, 2016;Newman, 2016) for roughly the same age groups. Newman (2016) reported that children 5-8 failed to show a relationship between addition performance and finger gnosis, while children 9-12 did show such a relationship; finger gnosis better predicted performance in older children than younger children. The explanation provided for the discrepancy, between the two age groups on how finger gnosis relates to addition performance, was that both addition and finger sense skills are still developing in the younger group.…”
Section: Discussionmentioning
confidence: 99%
“…Inspired from the association between digits and fingers observed in [10], we created a cognitive robotics model and performed a series of developmental learning experiments in which we simulate the learning of small number digits (1)(2)(3)(4)(5)(6)(7)(8)(9) without the association of robot's finger configurations.…”
Section: Discussionmentioning
confidence: 99%
“…Various embodied strategies, such as finger counting (for a recent special issue on the topic see [4]) and pointing gestures (e.g. [5]), can facilitate the acquisition of number cognition and predict mathematical achievement in children [6], [7]. Importantly, several studies suggest that finger processing may play a role in setting up the biological neural networks on which more advanced mathematical computations are built [8].…”
Section: Introductionmentioning
confidence: 99%
“…Because it was recently demonstrated that finger gnosis predicts a small part of variance in initial arithmetic competencies (Newman, 2016;Wasner, Nuerk, Martignon, Roesch, & Moeller, 2016), it could be interesting, in the future, to compare the efficiency of multisensory and finger-based intervention practices.…”
Section: Multisensory Versus Visual Trainingmentioning
confidence: 99%